Examining 5-Year Cervical Cytology Progression Among Minority Women Living With HIV and Baseline Negative Cytology. Issue 4 (October 2022) - Sanchez-Covarrubias, Alex P.; Crane, Joshua; Montgomerie, Emily K.; Potter, JoNell E.; Duthely, Lunthita M.; Bahadue, Felicia; Jeudin, Patricia P.
Abstract : Women living with HIV are at increased risk of developing cervical cancer, in a cohort of minority women living with HIV, human papillomavirus positivity predicted progression to low-grade/high-grade squamous intraepithelial lesions. Abstract : Objective: Women living with HIV (WLWH) have increased risk of human papillomavirus (HPV) infection, precancers, and invasive cervical cancers. This study aims to determine the rate of cervical cytologic progression and related factors in minority WLWH across 5 years. Materials and Methods: We used our HIV clinic database, complemented with a retrospective chart review to identify WLWH with a baseline negative cervical cytology between 2009 and 2012 and 5-year follow-up. Data included race/ethnicity, age, years living with HIV, AIDS status, viral load, history of smoking, drug use, and HPV status. Multivariate logistic regression tested progression of negative cytology to low-grade/high-grade squamous intraepithelial lesions (LGSIL/HGSIL). Results: Among 162 WLWH, 42% were African American, 30% non-Hispanic African Caribbean, and 26% Hispanic. At baseline, 21% had detectable viral load (>200 cp/mL), mean age was 44.8 (±11 years), and mean years living with HIV was 9.6 (±6.9). After 5 years, 19% of the cohort progressed to LGSIL/HGSIL. Human papillomavirus was detected consistently among women with cytologic changes (30% vs 7%, p < .01). Significant factors that predicted higher likelihood of progression to LGSIL/HGSIL were detection of HPV (adjusted odds ratios = 5.11 [1.31–19.93]; p = .02), and Centers for Disease Control and Prevention–defined AIDS status (adjusted odds ratios = 4.28 [1.04–17.63]; p = .04). Of the women who maintained negative cytology at 1 to 2 years (n = 102), 5 women (5%) progressed during the following 3 years before the recommended follow-up. Conclusions: Human papillomavirus detection and AIDS status were significant factors predicting progression to LGSIL/HGSIL among minority WLWH. Providers screening WLWH for cervical intraepithelial neoplasia should carefully decide screening intervals for minority populations.